Implementasi Fungsi Pengawasan Syariah terhadap Kepatuhan dan Risiko Pembiayaan di KSPPS BMT MAUNAH Desa Pacul Kabupaten Tegal - Lismoyo, Lismoyo (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to analyze the implementation of Sharia supervisory functions on compliance and financing risk at KSPPS BMT MAUNAH, Pacul Village, Tegal Regency. The research employs a descriptive qualitative approach using interviews, observations, and document analysis. The findings reveal that the Sharia Supervisory Board (DPS) plays a crucial role in ensuring that all operational and financing activities comply with Sharia principles. The supervision process includes contract verification, financing realization monitoring, and periodic Sharia audits. Although the institution’s Sharia compliance level reaches 85%, challenges remain, particularly regarding limited human resources and underdeveloped digital monitoring systems. Effective Sharia supervision has been shown to reduce non-performing financing (NPF) rates and enhance members’ trust in the institution. The study recommends strengthening the capacity of DPS through regular training, digitalization of Sharia audit reports, and the establishment of a risk-based monitoring system to improve the effectiveness of supervision at KSPPS BMT MAUNAH.